2015
DOI: 10.1111/gcb.12793
|View full text |Cite
|
Sign up to set email alerts
|

Rapid carbon turnover beneath shrub and tree vegetation is associated with low soil carbon stocks at a subarctic treeline

Abstract: Climate warming at high northern latitudes has caused substantial increases in plant productivity of tundra vegetation and an expansion of the range of deciduous shrub species. However significant the increase in carbon (C) contained within above-ground shrub biomass, it is modest in comparison with the amount of C stored in the soil in tundra ecosystems. Here, we use a ‘space-for-time’ approach to test the hypothesis that a shift from lower-productivity tundra heath to higher-productivity deciduous shrub vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
174
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(201 citation statements)
references
References 67 publications
(115 reference statements)
15
174
6
Order By: Relevance
“…7). This corresponds well with findings from field measurements and recent modeling studies that ECM are able to degrade complex N polymers in humus layers, thus enhancing soil N transformation under low-N conditions (Hartley et al, 2012;Moore et al, 2015;Lindahl and Tunlid, 2015;Parker et al, 2015;Baskaran et al, 2016). The modeled higher soil respiration further explains the minor losses of soil C and N at the southern sites and also a higher mineral N pool and thus higher N leaching in the explicit approach (Figs.…”
Section: Comparison Of the Three Ecm Modeling Approachessupporting
confidence: 91%
“…7). This corresponds well with findings from field measurements and recent modeling studies that ECM are able to degrade complex N polymers in humus layers, thus enhancing soil N transformation under low-N conditions (Hartley et al, 2012;Moore et al, 2015;Lindahl and Tunlid, 2015;Parker et al, 2015;Baskaran et al, 2016). The modeled higher soil respiration further explains the minor losses of soil C and N at the southern sites and also a higher mineral N pool and thus higher N leaching in the explicit approach (Figs.…”
Section: Comparison Of the Three Ecm Modeling Approachessupporting
confidence: 91%
“…, Parker et al. , ). In our study, deciduous shrub abundance under light grazing was 79% higher in warmed than control plots, while organic soil carbon stocks were 33% lower, which is comparable to the observed natural differences in soil organic carbon under varying deciduous shrub cover (Parker et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Parker et al. ). This warming and fertilization‐induced shift in shrub abundance, and thereby in the shrub‐mediated carbon sequestration processes, is unlikely to take place in high herbivore densities.…”
Section: Introductionmentioning
confidence: 99%
“…Afforestation in semiarid areas has been proposed as an effective way for improving soil carbon accumulation and restoration of degraded ecosystems (Lu et al, ; Shi et al, ). Nevertheless, field studies have shown diverse response of carbon stock to afforestation, observing increase (Garcia‐Franco et al, ), decrease (Berthrong, Jobbágy, & Jackson, ; Parker, Subke, & Wookey, ), and no change (Yang, Luo, et al, ). Our results indicated that afforestation of C. korshinskii only increased soil carbon stock in short term (10 years) compared with an abandoned field, but the carbon sink diminished during the late two decades (Figure a), which supported our primary hypothesis.…”
Section: Discussionmentioning
confidence: 99%